Research on aerobic fitness in children and adolescents: a bibliometric analysis based on the 100 most-cited articles - Xia, Rui; Yang, Liu; Liang, Chaomei; Lyu, Dongye; Zang, Wanli; Sun, Guanrong; Yan, Jin (Frontiers in Medicine, 2024)
This study aims to conduct a bibliometric analysis of the 100 most-cited articles to examine research trends, hot topics, and gaps in aerobic fitness research in children and adolescents, addressing the lack of evidence synthesis. Methods: The Web of Science Core Collection database was used for literature search, and bibliometric characteristics of the included research articles were imported and calculated. Descriptive statistics and visualisations by the VOS viewer were used for the presentation of bibliometric characteristics. Results: The 100 most cited articles received an average of 104 citations. British Journal of Sports Medicine and Medicine and Science in Sports and Exercise were the two top journals that published aerobic fitness research in children and adolescents. The United States was the top country that contributed to the most-cited research articles. Three top research topics were identified from the analysis, such as neuroscience, developmental psychology, and aerobic health. Conclusion: Aerobic fitness research in children and adolescents has received much attention and interest since 2000. The most contributing authors in this research field were from developed countries, such as the United States, and cognition and health-related research were priorities.